2014
DOI: 10.2320/matertrans.m2014041
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Segregation and Microstructural Characteristics in Rheo-Diecasting of a High Strength Al–4.8 mass%Si–0.7 mass%Mg Alloy

Abstract: Rheo-diecasting with electro-magnetic stirring has been carried out to investigate macro-segregation and microstructural characteristics of a high strength AlSiMg alloy under various process conditions. The amount of initial heterogeneous nucleation and the degree of temperature uniformity in the slurry are dependent on the superheat of the melt at pouring into the slurry making vessel. The formation of macro-segregation in rheo-diecasting was closely related to the microstructural characteristics of semi-soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the experiment, we found that this segregation within the same sheet sample was nearly changeless along the flow direction. The distribution of the primary phase, namely the macrostructural uniformity, is also an important factor effecting the final property of the castings [21,22]. Therefore, the distributions of primary α-Mg in the cross-sections of the samples have also been investigated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In the experiment, we found that this segregation within the same sheet sample was nearly changeless along the flow direction. The distribution of the primary phase, namely the macrostructural uniformity, is also an important factor effecting the final property of the castings [21,22]. Therefore, the distributions of primary α-Mg in the cross-sections of the samples have also been investigated.…”
Section: Figurementioning
confidence: 99%
“…At the same velocity, when the solid fraction was increased to 0.61 (Figure 10c), a more serious α-Mg segregation along the sample thickness formed, and the width of the segregation layer was approximately 0.8 mm. However, when the injection velocity was increased to 3 m/s (Figure 10b), the distribution of primary α-Mg along the sample The distribution of the primary phase, namely the macrostructural uniformity, is also an important factor effecting the final property of the castings [21,22]. Therefore, the distributions of primary α-Mg in the cross-sections of the samples have also been investigated.…”
Section: Figurementioning
confidence: 99%
“…7,8) In semi-solid metal forming, the final solidification microstructures are greatly dependent upon the microstructures of semi-solid slurries, which are closely related to the superheat of the melt in making slurries. 15) Three types of semi-solid slurries which are shown in Fig. 2(a)(c) were used in semi-solid forging to investigate the influence of microstructures of semi-solid slurries on the formation of macro-segregation.…”
Section: Segregation Behavior In Semi-solid Forgingmentioning
confidence: 99%